2017
DOI: 10.1155/2017/8983958
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Response to Cysticidal Therapy, and Risk Factors for Persistent Seizure in Indian Children with Neurocysticercosis

Abstract: Background. Neurocysticercosis (NCC) is the commonest cause of childhood acquired epilepsy in developing countries. The use of cysticidal therapy in NCC, except “single lesion NCC,” is still debated in view of its doubtful usefulness and potential adverse effects. Methods. Children presenting with first episode of seizure or acute focal neurological deficit without fever were screened for NCC and received appropriate therapy (followup done for 1 year to look for the response and side effects). Results. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…9 Kumar et al, also reported a dominance of males (55.8%). 18 These findings in general suggest that gender related differences in different studies are incidental and does not indicate any gender associated risk of seizures.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…9 Kumar et al, also reported a dominance of males (55.8%). 18 These findings in general suggest that gender related differences in different studies are incidental and does not indicate any gender associated risk of seizures.…”
Section: Discussionmentioning
confidence: 88%
“…This finding is similar to the observation of Kumar et al, who in a study of 120 cases of NCC reported a dominance of non-vegetarians (64.2%), however, Pandit et al, in their study of 50 cases of NCC had only 32% nonvegetarians. 18,20 These findings suggest that nonvegetarian diet necessarily need not be the source of transmission of NCC.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…However, NCC is responsible for a non-negligible portion of epilepsy cases in children as well. In Northern India, the reported NCC prevalence was 4.5% among children aged 1 to 14 years presenting to a tertiary care hospital with a first episode of seizure or acute focal neurological deficit [ 12 ]. According to another community-based study conducted in the city of Kolkata, India, the prevalence of NCC among patients aged 19 years or less with active epilepsy was 23.4% [ 13 ].…”
Section: Introductionmentioning
confidence: 99%